The Impact of Talent Leadership on Attracting and Retaining High Value Professors at Historically Disadvantaged Higher Education Institutions in South Africa - Mabasa, Fumani; Morukhu, Doreen; Maluka, Rivalani Harriet (Profesional Muda Cendekia Publishing, 2024)
Research Aims: This study aimed to investigate the impact of talent leadership on attracting and retaining high-value professors at HDHEIs in South Africa. Design/methodology/approach: A qualitative approach was used, with 20 face-to-face interviews and document analysis with academic leaders from five HDHEIs. Thematic analysis used to analyse the collected data. Research Findings: The findings revealed five themes regarding the impact of talent leadership at HDHEIs: empowerment, motivation, engagement, commitment, and competence among professoriate staff at the university. Theoretical Contribution/Originality: This study demonstrates the significance of talent leadership in providing a sense of belonging, respect, personal growth, and development to the professoriate, all of which are necessary for attracting and retaining high-value professors. Recommendations stemming from the study encompass targeted leadership training programs, the establishment of mentorship initiatives, and the implementation of inclusive and supportive policies. These recommendations are intended to guide HDHEIs in South Africa toward fostering an environment that not only attracts but also retains high-value professors, ultimately contributing to the sustained growth and development of these South African institutions.